KESALEHAN SOSIAL SEBAGAI RITUAL KELAS MENENGAH MUSLIM - Jati Raharjo Wasisto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
The emergence of social piety is an interesting phenomenon among recent middle class Indonesian muslim. The aims and scope of social piety which established is to redefine spirituality. Process of reconstucting social piety can be traced from the intersection from both material and spiritual aspect. Spiritual is a holy effort to pray God and material can be analyzed as a complementer factor in spirtual effort. To become pious man is the main thing however the most intention are both recognition and representation from others. This article will elaborate more deeply about the meaning of social piety in recent middle class Indonesian muslim.